Features of Breast Cancer Progression after Comprehensive Treatment, Prognosis of Metastatic Spread - Yu. Chuprovska; V. Bodiaka; O. Ivashchuk; Ch. Tsagkaris (Львівський клінічний вісник, 2025)
Introduction. The effectiveness of breast cancer treatment is directly related to the absence of metastatic spread after comprehensive treatment. Still, there are no clear criteria and algorithms for predicting the occurrence of this complication.